Plurality Awareness In Surakarta-Indonesia: Conflict of Map, Awareness of Elite, and Future Challenges - Faishol, Abd. (Indonesian Journal of Islamic Literature and Muslim Society, 2021)
The purpose of the study is to describe pluralism in society and active efforts or positive interactions in the pluralistic environment to create harmony, tolerance, and mutual respect. This research employs qualitative analysis and descriptive analysis as its technique for analyzing the data. The researcher uses his logic when discussing this research, in which the researcher is an instrument of the research. The validity of the result of this research is carried out by data triangulation analysis. The process of validating the result is also carried out with a focus group discussion which involves seven expert lecturers in the history of civilization. In practice, recognition can be made verbally, in documents, and in behavior (attitude). Active efforts or positive interactions can be in the form of mutual cooperation activities, willingness to get along, helping each other, visiting each other, gathering in a forum to solve a problem, or other activities. In principle, conflicts that have occurred in Surakarta can be identified and triggered by several factors: ethnics factors; political factors (macro politics, national and micropolitics, regional; economic factors (the dominant factor); the factor of social segregation, which consists of social segregation based on ethnic trading area, social segregation based on religious territory, and cultural segregation between the Kasunanan and Mangkunegaran communities having different characteristics.